Penerapan Intervensi Terapi Reflexology Terhadap Penurunan Intensitas Nyeri Post Histerektomi Dengan Mioma Uteri - Aura Zahra Oceani D; Nur Azizah Indriastuti (Pusat Riset dan Inovasi Nasional, 2023)
Hysterectomy is a surgical procedure for removing all or part of the uterus due to gynecological diseases, one of which is uterine myoma. The impact that is often felt by patients after surgery is the presence of incisions and damaged tissue causing a sensation of pain. Reflexology therapy as a non-pharmacological action is a new innovation for reducing pain with a very simple relaxation method. This case study aims to determine the application of reflexology therapy to reduce pain levels in postoperative hysterectomy patients. The method in this research is a case study in post hysterectomy patients who experience complaints of pain. The instrument used is using a Numeric rating scale (NRS) with finger-hand relaxation intervention given for 3 days. The results of this case study showed that by doing reflexology therapy for 3 days there was a significant decrease in pain levels from a scale of 5 to a scale of 2. The effectiveness of applying standard nursing care in reducing the level of pain given to patients showed a decrease in pain levels from the first day of intervention to the first day of intervention third.